Мовленнєво-музичний твір як елемент пісенного дискурсу - Марченко, Валентина Володимирівна; Marchenko, V. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті на основі аналізу теоретичних й експериментальних робіт комунікативно-когнітивного напряму лінгвістичних досліджень з’ясовано природу пісенного дискурсу та особливостей функціонування у ньому мовленнєво-музичних творів. Зазначено перспективність вивчення особливостей функціонування інтонації мовлення та інтонації мовленнєво-музичних творів у площині комунікативно-когнітивної парадигми. In the paper, basing on the analysis of theoretical and experimental studies of cognitive and communicative direction of linguistic research, the author makes an attempt to explain the nature of the song discourse and functioning of speech-and-music works as its element. The author views speech-and-music works as a product of speech-and-music communication, as a complex system formed as a result of the synergetic integrity of the components of a sender’s text and music culture and can be adequately decoded by the recipient in the case of the intersection of mental culture spheres of the communication participants. The author states on the perspective of studying the functioning of intonation of speech and speech-and-music works in the frameworks of communicative and cognitive paradigm.
Speech-and-music Works as an Element of Song Discourse
Keywords: мовленєво-музичний твір; speech-and-music works; пісенний дискурс; song discourse; текст; text